Diagnóstico de enfermagem risco de quedas em pacientes com angina instável - Vitor, Allyne Fortes (2010)
The risk for falls can be recognized as a phenomenon or a nursing diagnosis. Investigations have related directly myocardial ischemia, such as unstable angina and risk of falls. This study aimed to analyze the nursing diagnosis risk of falls in the occurrence of unstable angina by a cross-sectional study in 57 patients admitted in a teaching hospital, and through physical examination form. For statistic analysis, we used chi-square test, Fisher exact test, Mann-Whitney, t-test and coeffi cient Phi (p <0.05). The Risk of falls was the most prevalent nursing diagnosis (87.71%), especially in men, older, less educated as well as poorest people. The presence of unstable angina, hypertension, antihypertensive drugs, vascular disease, visual diffi culties, and insomnia were associated with that nursing diagnosis. The development of clear parameters to measure more accurately the risk of falls in hospitals is essential.